2020
DOI: 10.1016/j.mri.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A 16-channel loop array for in vivo macaque whole-brain imaging at 3 T

Abstract: Non-human primates (NHPs) are vital models for neuroscience research. These animals have been widely used in behavioral, electrophysiological, molecular, and more recently, multimodal neuroimaging and neuro-engineering studies. Several RF coil arrays have been designed for functional, high-resolution brain magnetic resonance imaging (MRI), but few have been designed to accommodate multimodal devices. In the present study, a 16-channel array coil was constructed for brain imaging of macaques at 3 Tesla (3T). To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The large singe-channel surface loopole coil is a practical and feasible tool for awake monkey brain imaging in neuroscience, in which the space for device mounting is very limited especially in conjunction with closefitting receive arrays such as reported in Quan et al (2020). The improvement of + B 1 uniformity was significant, and meanwhile it was observed that the unique use of inductors in the circuit further improved the + B 1 uniformity and reduced the maximum local SAR values in the entire object.…”
Section: Discussionmentioning
confidence: 99%
“…The large singe-channel surface loopole coil is a practical and feasible tool for awake monkey brain imaging in neuroscience, in which the space for device mounting is very limited especially in conjunction with closefitting receive arrays such as reported in Quan et al (2020). The improvement of + B 1 uniformity was significant, and meanwhile it was observed that the unique use of inductors in the circuit further improved the + B 1 uniformity and reduced the maximum local SAR values in the entire object.…”
Section: Discussionmentioning
confidence: 99%
“…The need for stability of longitudinal studies can therefore be in conflict with the drive for methodological and technical improvement, especially when imaging facilities and equipment are shared by multiple research groups. Moreover, to assure stable image quality, the head of the animal needs to be consistently positioned in the scanner field across scans and various custom radiofrequency coils for NHPs have been presented in recent years to help address this issue ( Belcher et al., 2013 , Gilbert et al., 2019 , Quan et al., 2020 ). A potential risk is that experimenters become more proficient over time at positioning the heads of animals relative to the coils and the magnet, which can have an impact on image quality, especially when one uses non-standardized arrangements of surface coils.…”
Section: Challenges Of Longitudinal Mri Datasetsmentioning
confidence: 99%
“…The use of contrast agents, improved sequences, and high-field magnets is increasing the signal-to-noise ratio and spatial resolution into the realm where subcortical activations can be reproducibly detected (e.g., Baker et al, 2006;Ortiz-Rios et al, 2015;Quan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%